Fear - Candau, Brittany (Los Angeles, Calif. : Disney Press, 2015)
Dive inside Riley's mind and get to know the Emotions that know her best with this unique format. With five fun storybooks, each devoted to a different Emotion, as well as a die-cut slipcase, fans of Pixar's upcoming film, Inside Out, will treasure this special collection of Joy, Sadness, Fear, Anger, and Disgust."--Provided by publisher